Effects of aggregate microstructure on slag resistance of lightweight Al2O3-MgO castable. Issue 18 (15th December 2017) - Zou, Yang; Gu, Huazhi; Huang, Ao; Zhang, Meijie; Zhang, Mintao
Abstract: Corundum-spinel castables using lightweight aggregate have drawn much attention due to their energy-saving potential, in particular when they are applied in high-temperature areas, such as the work lining of refining ladle. One of the main issues which hinder their application is their relatively poor slag corrosion performance. In this study, one type of dense tabular corundum and three types of lightweight corundum were chosen as aggregates to prepare four different model corundum-spinel castables. Their slag resistance was evaluated by an induction furnace corrosion test method. As well as SEM, EDS, and XRD characterizations, thermodynamic and kinetic analyses were carried out to assist understanding the corrosion mechanism. Results indicated that size and shape of crystalline grain in aggregate were important for the slag corrosion (dissolution) resistance of lightweight corundum-spinel castables under dynamic condition (enforced convection), whereas the effects of pore characteristics were not significant. Use of aggregates having large average crystal size and flake-shaped crystals led to a thicker diffusion boundary layer and lowered dissolution rate, i.e., good corrosion resistance, whereas use of aggregates with small and spherical crystals and larger pores led to poor slag resistance.